Referendums, democracy and separatism - Qvortrup, Matt (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There have been referendums on separatism for longer than there has been democracy. Allowing areas to vote on independence or on whether to belong to another state or territory is a practice that goes back as far as the 14th century, though it is only in the 20th century that it really took off. While many claim a right to "self-determination", there is no formal legal right to hold referendums on secession, unless there are constitutional provisions for this, a specific agreement between the parties, or if the country is a former colony. Of the referendums on independence that have been held, very few have yielded "yes" votes in developed democratic societies.
Keywords: referendums; nationalism; secession; independence; democracy; Caledonia